Hesperetin mitigates acrolein-induced apoptosis in lung cells in vitro and in vivo - Jung Hyun Park; Hyeong Jun Ku; Jeen-Woo Park (Taylor & Francis Group, 2018)
Objectives: A number of studies have suggested that acrolein-induced lung injury and pulmonary diseases are associated with the depletion of antioxidants and the production of reactive oxygen species. Therefore, compounds that scavenge reactive oxygen species may exert protective effects against acrolein-induced apoptosis. Because hesperetin, a natural flavonoid, has been reported to have an antioxidant activity, we investigated the effect of hesperitin against acrolein-induced apoptosis of lung cells. Methods: We evaluated the protective role of hesperetin in acrolein-induced lung injury using Lewis lung carcinoma (LLC) cells and mice. Results: Upon exposure of LLC cells and mice to acrolein, hesperetin ameliorated the lung inbjury through attenuation of oxidative stress. Conclusion: In the present report, we demonstrate that hesperetin exhibits a protective effect against acrolein-induced apoptosis of lung cells in both in vitro and in vivo models. Our study provides a useful model to investigate the potential application of hesperetin for the prevention of lung diseases associated with acrolein toxicity.